CLICK & SHOP: A MODERN E-COMMERCE WEB APPLICATION - Srivastava, Raj; Dubey, Ranjeet; Kumar, Shivam; Gupta, Shivam; Singh, Janhvi; Sharma, Chanchal (International Journal of Engineering Technologies and Management Research, 2025)
The rapid growth of online retail necessitates 2. Secure Transactions: Incorporate secure payment the development of dynamic, scalable, and user-centric e- gateways and data protection measures to safeguard commerce platforms. "Click & Shop" is a modern web user information and build trust in the platform's application built with React.js, designed to deliver a seamless reliability. shopping experience across devices. Leveraging React's 3. Efficient Product Management: Develop a robust component-based architecture, the application ensures back-end system that allows administrators to efficient rendering and state management, facilitating real- manage product listings, inventory, and order time updates and interactive user interfaces. Key features of processing effectively, ensuring smooth operational "Click & Shop" include a comprehensive product catalog, workflows. intuitive search and filtering options, a secure shopping cart, 4. Scalability: Design the application architecture to and streamlined checkout processes. The integration of accommodate future growth, enabling the addition Firebase enhances the application's capabilities by providing of new features, products, and services without robust backend support for user authentication, real-time compromising performance. database management, and hosting services. 5. Data-Driven Insights: Integrate analytics tools to monitor user behaviour, sales trends, and other key